A Study of Maintaining and Improving the WASH Services Provided by Local and International Agencies in Selected Refugee Camps in Kurdistan Region, IRAQ - Ahmed, Sarko Sabir (European Journal of Sustainable Development, 2016)
Hosting a massive number of refugee in Kurdistan Region of Iraq which is above 2 million people in both category of internal displaced people and refugees, while the technical and economical capacities of the local government are limited which results the provision of water, sanitation and hygiene challenging for both local people and the surrounding environment. The aim of this research is benchmarking the current WASH services in the existing refugee camps, identifying the major difficulties within WASH service provision and highlighting the impact of current WASH practices on physical environment. The intervention of this research includes the camps in both Erbil and Sulaimanyah provinces of Iraqi-Kurdistan. The international and local agencies have been evaluated regarding WASH services provision in selected refugee camps. Detailed interviews were conducted with 6 service provision agencies’ representatives to record their approaches while, questionnaire was administered among 395 refugees in addition with personal observation to determine at what extend the services are adequate and sustainable. It has been observed that both local and international organizations claimed to have sufficient WASH services but on ground, there are big challenges facing the process of WASH service provision. In general, it has been found that, most of the service providers are not concern with environmental risks which may cause by lack of sufficient WASH services. . There are several environmental issues in the camps, including lowering groundwater table, and increasing soil pollution as a result of unmanaged wastewater disposal and Excreta management. Public health problems in the camps are due to dispose black water into the pits while the groundwater is the main water supply source in the refugee camp. Keywords: Water, Sanitation, Hygiene, Environment, Waste Management, Groundwater